Ferns and fern allies of District Shopian, Kashmir Valley, India (Biodiversitas Journal of Biological Diversity, 2014)
Mir SA, Mishra AK, Pala SA, Reshi ZA, Sharma MP. Ferns and fern allies of District Shopian, Kashmir Valley, IndiaBiodiversitas 16: 27-43. Shopian, recently created hilly district of Kashmir valley, Jammu and Kashmir is surrounded by the loftymountains of Pir-Panjal range. More than half area of district is occupied by different forests, subalpine, alpine and mountainous zones.Great altitudinal variation, adequate rainfall, high forest cover, large number of streams, springs and topographic variations render thedistrict worthy for supporting rich fern flora. Therefore, the current study was aimed to undertake in-depth systematic survey of differenthabitats of Shopian for the collection of diversity of pteridophytes. Specimens were collected during 2010, 2011 and 2012 growingseasons from June to November. A total 81 species of ferns and fern allies belonging 27 genera and 11 families were reported. Thedominant families of the region are Dryopteridaceae (25 species) followed by Woodsiaceae (16 species), Aspleniaceae (13 species) andPteridaceae (12 species). Similarly, the dominant genera collected from here are Dryopteris (14 species), Asplenium (13), Polystichum(11 species) and Athyrium (6 species). A list of the fern and fern allies, along with update nomenclature, their selected Synonym,diagnostic features, distributional and ecological notes have been provided here.
Keywords: distribution, diversity, ferns, Kashmir valley, lycophytes, Shopian, survey